2/5(2x+8)=2(2-3x)+6

Simple and best practice solution for 2/5(2x+8)=2(2-3x)+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2/5(2x+8)=2(2-3x)+6 equation:



2/5(2x+8)=2(2-3x)+6
We move all terms to the left:
2/5(2x+8)-(2(2-3x)+6)=0
Domain of the equation: 5(2x+8)!=0
x∈R
We add all the numbers together, and all the variables
2/5(2x+8)-(2(-3x+2)+6)=0
We multiply all the terms by the denominator
-((2(-3x+2)+6))*5(2x+8)+2=0
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8
We calculate terms in parentheses: -((2(-3x+2)+6))*5(2x+8), so:
(2(-3x+2)+6))*5(2x+8

See similar equations:

| 12u-2u-8=18 | | 3×(x-1)-2×(×-2)=2x-2 | | 2/5g=14 | | m–35=21 | | 6y-5=5y+9 | | 12u-2u=18 | | 9+5a=2a+9a | | -3.6q=-13.14-4.5q | | r/9=-13 | | 13r-9r=20 | | 7(c-17=-49 | | 15b-14b=10 | | 16-4n=n-8-2n | | 2^n•2^6=2^4 | | 4n+n=4n+7 | | 6.3-15.1t+12.33=-15.2t+17.73 | | 23x+7+8+18x=360 | | 7a-a=6 | | 5(r+2)=7r | | -280/99=21/11x | | -3s=-4-s | | 9x^2-115x+300=0 | | 4c+10=c | | 11-3v=-19-20+2v | | 3(c−12)=−9 | | 2r+10=4 | | -4d=-5d+12 | | 1/3(18-6x)=10 | | -10+7p-8=-6+9p | | 8k+7=71 | | 4+4n=-9n+4 | | 9b+19=-17+6b |

Equations solver categories